An n-ary zipWith in Haskell - Fridlender, Daniel; Indrika, Mia (BRICS Report Series, 1998)
The aim of this note is to present an alternative definition of the zipWith family in the Haskell Library Report [5]. Because of the difficulties in defining a well-typed function with a variable number of arguments, [5] presents a family of zipWith functions. It provides zip functions zipWith2, zipWith3, . . . , zipWith7. For each n, zipWithn zips n lists with a n-ary function. Defining a single zipWith function with a variable number of arguments seems to require dependent types. Inspired by [3], we show, however, how to define such a function in Haskell by means of a binary operator for grouping its arguments. For comparison, we also give definitions of zipWith in languages with dependent types.